2020
DOI: 10.1093/femsle/fnaa118
|View full text |Cite
|
Sign up to set email alerts
|

Membrane transporters in the bioproduction of organic acids: state of the art and future perspectives for industrial applications

Abstract: Organic acids such as monocarboxylic acids, dicarboxylic acids or even more complex molecules such as sugar acids, have displayed great applicability in the industry as these compounds are used as platform chemicals for polymer, food, agricultural and pharmaceutical sectors. Chemical synthesis of these compounds from petroleum derivatives is currently their major source of production. However, increasing environmental concerns have prompted the production of organic acids by microorganisms. The current trend i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 131 publications
0
27
0
Order By: Relevance
“…These results demonstrated that C4-dicarboxylic acid transporters from different species can enhance the extracellular secretion of SA in Y. lipolytica . Among these transporters, SpMae1 has been widely applied to improve the microbial production of malate, succinate and fumarate [ 30 , 31 , 33 ], thus it can be used in the subsequent modification to obtain the SA over-production strains.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrated that C4-dicarboxylic acid transporters from different species can enhance the extracellular secretion of SA in Y. lipolytica . Among these transporters, SpMae1 has been widely applied to improve the microbial production of malate, succinate and fumarate [ 30 , 31 , 33 ], thus it can be used in the subsequent modification to obtain the SA over-production strains.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The production of biocompounds in high yields requires the optimization of several processes, including membrane transport of solutes to improve the entrance of substrates in the cell, exchange of products within cell organelles, and the efflux of metabolites to the extracellular medium, increasing the cell’s tolerance to toxic final products, and decreasing downstream processing costs [ 109 ]. In C. jadinii , several plasma transporters were physiologically or genetically characterized ( Figure 3 ).…”
Section: Membrane Transporters Characterized In C Jadinmentioning
confidence: 99%
“…The expression of membrane transporters allied to metabolic engineering tools is crucial to develop new and more efficient strains to produce bio-based compounds. Thus, increased knowledge of transporter proteins will enable the development of improved cell factories [ 109 , 143 , 144 ].…”
Section: Membrane Transporters Characterized In C Jadinmentioning
confidence: 99%
“…Therefore, a proper export of the products of interest is often indispensable for a profitable and efficient cell factory. Researchers have been focusing on maximizing the export of the compounds of interest by overexpressing specific membrane transporters, engineering transporters for improved efficiency or even introducing heterologous transporters in the cell factory ( Boyarskiy and Tullman-Ercek, 2015 ; Kell et al, 2015 ; Erian et al, 2020 ; Soares-Silva et al, 2020 ). For more detailed information on the engineering of membrane transporters for industrial biotechnology applications, the reader should look the works mentioned above.…”
Section: Membrane Engineering In Microbial Workhorsesmentioning
confidence: 99%